Characterization and Tensile Fractography of Nano ZrO2 Reinforced Copper-Zinc Alloy Composites - Madeva Nagaral; Prasad H. Nayak; H. K. Srinivas; V. Auradi (Fracture and Structural Integrity)
Nano particulates fortified metal lattice composites are finding extensive variety of utilizations in car and sports hardware fabricating businesses. In the present investigation, an endeavor has been made to create copper-zinc-nano ZrO2 particulates strengthened composites by utilizing fluid liquefy technique. 4, 8 and 12 wt. % of nano ZrO2 particulates were added to the Cu-Zn base grid. Microstructural studies were finished by utilizing SEM and EDS examination. Mechanical behavior of Cu-Zn-4, 8, 12 wt. % of nano ZrO2 composites were assessed according to ASTM benchmarks. Checking electron micrographs uncovered the uniform dispersion of nano ZrO2 particulates in the copper zinc composite network. EDS examination affirmed the nearness of Zr and O components in nano ZrO2 strengthened composites. Further, it was noticed that hardness, UTS, yield quality of Cu-Zn composite expanded with the expansion of 4, 8 and 12 wt. % of nano ZrO2 particulates. Ductility of nano composites was decreased by adding zirconium oxide particulates. Fractography of tensile specimens were carried out by using SEM micrographs to understand the failure mechanisms.